Spatial Incidence and Characteristics of Microplastics Around Industrial Zones (Case Study: Surabaya Industrial Estate Rungkut, Indonesia) - Haribowo, Riyanto; Shiddik, Muchammad Ja'far; Wirawan Putra, Rizky Almarendra; Anggani, Tsabita Putri; Wahyuni, Sri; Prasetyorini, Linda; Fadhillah, Arriel (Fakultas Teknik, Universitas Brawijaya, 2024)
Microplastics found in drainage channels are a significant contributor to river pollution. Among the potential contributors to this issue are industrial activities. In this investigation, we focused on assessing the occurrence of microplastics within the Surabaya Industrial Estate Rungkut (SIER) industrial area, which discharges into the Tambakoso River in East Java, Indonesia. Surface water tests were obtained from 19 particular focuses. The extraction of microplastics included filtration, wet peroxide oxidation, and density separation techniques. Recognizable proof of polymers was accomplished utilizing Fourier change infrared (FTIR) spectroscopy. Statistical analysis was conducted employing the Ward cluster test method within the IBM SPSS Statistics software. The findings revealed a gradual increase in the abundance of MPs from upstream to downstream locations, with the highest concentration observed at point 19 (548.33 particles/L). The majority of microplastics were characterized by their small size (<1 mm), fragment shape (45.93%), and black color (56.18%). The types of polymers are mostly polypropylene (PP) and polyethylene (PE). Findings derived from the cluster analysis highlight the substantial involvement of the food and beverage, pharmaceutical, and plastics sectors in microplastic pollution within the drainage channels of the SIER industrial zones.